Politician’s Strategy After The Pandemic: Strengthening of Patronage Goods in The Form of Social Assistance - Ferhadz Ammar Muhammad (Institut Teknologi Sepuluh Nopember, 2020)
This research describes and analyzes the strategies of politicians to attract voter support in electoral politics by providing patronage goods or club goods. The study of this strategy is increasingly relevant considering the Covid-19 pandemic that has emphasized to political actors the importance of social assistance (in Indonesian: bansos,etc.). In some areas, especially those with a flow-political landscape in the form of strong links between parties and social and religious organizations, it shows that local politicians are cooperating with organizations that share a platform with parties to distribute social assistance. However, this research confirms the academics' opinion, such as Edward Aspinall, who believe that giving from politicians with the motive of gaining mass support for party interests, and of course electoral politics, can be said to be an affirmation of patronage democracy. Through comparative analysis with several cases of social assistance distribution that have existed, this study strengthens the main thesis about patronage items as a binding of loyalty between the mass of voters whose numbers are very beneficial for parties and party politicians.